Efektivitas Penggunaan Blended Learning dengan Platform Quipper School terhadap Hasil Belajar Peserta Didik Mata Pelajaran Biologi Kelas XI MIPA di SMAN 2 SELONG. - Ermila Mahariyanti; Samsul Hadi (Peneliti.net, 2020)
This study was aim to determine the effectiveness of using Blended Learning with the Quipper School Platform towards students’ learning outcomes in biology class XI MIPA. Type of the study was quasi experimental research. The population of the study was all students of class XI MIPA SMAN 2 Selong. Meanwhile, the samples were two classes randomly taking from five classes. The samples obtained were class XI MIPA 5 as the experimental class and class XI MIPA 4 as the control class. Multiple choice test was used as The instrument to collect data on students’ learning outcomes. Hypothesis testing was carried out using the SPSS 16.0 program with the T test at the 5% significance level. Prerequisite test is carried out before hypothesis testing namely normality and homogeneity data. The results of the significance value obtained for the normality of the control class and experimental class data were> 0.05, so it can be concluded that the data is normally distributed. Meanwhile, for the data homogeneity test, the results obtained a significance value> 0.05 and it can be concluded that the data has a homogeneous variance. The results of hypothesis testing using the T test obtained a significance value of 0.003. Because the significance value <0.05, it can be concluded that the use of Blended Learning with the Quipper School Platform is effective towards students’ learning outcomes in biology class XI MIPA.